Correlation between Serum IL-17 Levels and 24-H Urinary Protein in Lupus Nephritis Patients at Ulin General Hospital Banjarmasin: A Cross-Sectional Study - Felix Hariyanto Salim (Indonesian Rheumatology Associantion, 2025)
24-h urinary protein is a marker and predictor of kidney function in Lupus Nephritis (LN). IL-17 appears to contribute to LN. The aim of this study was to determine the correlation between serum IL-17 levels and 24-h urinary protein in LN patients.